Emissions from MDF: Governing Factors and Mitigation Strategies. (4th July 2019) - Korenberg, Capucine; Bertolotti, Giulia
ABSTRACT: Many museums use elements, such as baseboards and inserts, made of medium density fibreboard (MDF) inside showcases. MDF is manufactured by bonding wood fibres with a resin. It emits volatile compounds that can be harmful to a wide range of museum objects, including formaldehyde. There is currently no entirely effective method to block emissions from MDF and MDF, even sealed, should not be used in long-term displays. Because of the risk posed by formaldehyde to humans, there has been much research in the wood panel industry on the emissions from composite wood. These studies have shown that many factors such as the resin, the wood species of the fibres, the pressing temperature, time elapsed since manufacture, ambient conditions etc., affect the off-gassing of composite wood. All these factors need to be taken into consideration when selecting MDF to be used in showcases or when investigating the use of barrier films and liquid sealants to reduce emissions from MDF. Unfortunately, the findings of industrial research are not widely known in the cultural heritage sector and studies investigating mitigation strategies for MDF emissions have not taken into account these factors, leading to possibly unreliable results. The goal of this article is to review research on the emissions from MDF from a range of fields including conservation, composite wood manufacture, corrosion science, and air pollution. It includes a description of the factors governing the emissions from MDF and a critical review of strategies used to reduce these emissions.